2021
DOI: 10.1080/10872981.2021.1936435
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on project ECHO: qualitative findings from five different ECHO programs

Abstract: Project ECHO (Extension for Community Healthcare Outcomes) was developed in 2003 as an innovative model to facilitate continuing education and professional development. ECHO emphasizes ‘moving knowledge, not people.’ To accomplish this, ECHO programs use virtual collaboration and case-based learning to allow practitioners, including those in rural and underserved areas, to receive specialist training. The ECHO model has expanded rapidly and is now used in 44 countries. Preliminary research on ECHO’s efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Our analysis suggests that while telehealth use in the primary care setting was largely limited before the pandemic to those with prior training and those in the South and West—where project ECHO may have increased participation in rural communities, 37 - 39 the pandemic has spurred innovation in care delivery, with younger physicians, Asian physicians, and those without formal training in medical school leading the change. While some of these trends were expected—for example younger physicians who are more comfortable with technology being more likely to adopt telehealth—other findings like Asian physicians being significantly more likely to increase their telehealth use are less easily explained.…”
Section: Discussionmentioning
confidence: 94%
“…Our analysis suggests that while telehealth use in the primary care setting was largely limited before the pandemic to those with prior training and those in the South and West—where project ECHO may have increased participation in rural communities, 37 - 39 the pandemic has spurred innovation in care delivery, with younger physicians, Asian physicians, and those without formal training in medical school leading the change. While some of these trends were expected—for example younger physicians who are more comfortable with technology being more likely to adopt telehealth—other findings like Asian physicians being significantly more likely to increase their telehealth use are less easily explained.…”
Section: Discussionmentioning
confidence: 94%
“…Preliminary data on the ECHO model's effectiveness in pain management, cancer prevention, and HIV are promising. 20 The Alzheimer's Association has partnered with Project ECH-O to provide education on Alzheimer's diagnosis and care. In a six-month program, primary care providers participate in case-based learning led by dementia experts on topics such as evaluation and diagnosis of dementia, care planning, and care management.…”
Section: Capabilitymentioning
confidence: 99%
“…Since then, the ECHO model has expanded significantly, with over 49 countries delivering 955 ECHO projects across a range of areas within healthcare (including behavioural/mental health, chronic pain, HIV, geriatrics and cancer care) and beyond [ 2 , 4 – 6 ]. Numerous studies have shown that ECHO expands PCP knowledge of best practices, increases self-efficacy and behaviour, and improves patient outcomes as well as cost-effectiveness [ 1 , 7 10 ] Additionally, several qualitative studies have suggested that ECHO programmes can serve to reduce providers’ feelings of isolation or help create a community of practice [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%